IDENTIFIKASI FAKTOR PENENTU PROFITABILITAS BPR KONVENSIONAL DI PROVINSI BALI - Devy, Tripeny Rosmala; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Profitability is the bank's ability to gain profits which can show good bank performance. The purpose of this study was to determine the effect of capital adequacy, credit risk and liquidity risk on BPR profitability with a sample of 47 BPRs for the 2017-2021 period. The analysis technique in this study used multiple linear regression analysis techniques. Based on the test results that have been carried out, capital adequacy (X1) and credit risk (X2) have a negative effect on BPR profitability and liquidity risk (X2) has a positive effect on BPR profitability in the Province of Bali. The implication of this research is that BPR’s determine the appropriate lending ceiling based on capital considerations that can later have an impact on BPR profitability.